(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
A monopanel is the system building witch consists of two thin ferrocement block as a faces and between them a bushy layer of low strength, density and cost as a core made from lightweight material for example from polystyrene foam as using in this investigation or any material as an insulation . The simple structural idealization of a monopanel system is that the core provides transverse trusses between the faces that prevent flexural ,shear force and compression. Transverse trusses made of steel bars having a diameter of 3.2 mm, which make available as tie reinforcement to prevent the thin ferrocement skins from local buckling, have been used in the present work. These transfer system consist of two longitudinal bars connected by inclined steel bar forming trusses shape making an angle equals to 60o with the longitudinal bars. The main object of this research is to present an experimental investigation on the behavior and load carrying capacity of monopanel beams. The experimental work includes testing six groups of monopanel beams, and has been investigated the effect of a different depths of monopanel beams and number of layer of wire mesh of skin faces (one or two layers ) on the behavior and the ultimate load capacity. Also comparison of these results with the ACI code 318M-08 formulations have been made.